Possible underascertainment of variant Creutzfeldt-Jakob disease: a systematic study. Issue 3 (1st March 2002) - Hillier, C E M; Salmon, R L; Neal, J W; Hilton, D A
Abstract : Objectives: To predict the size of the vCJD epidemic it is important to know whether the description of cases of vCJD in 1996 represent the first cases of a new disease entity or whether detection was due to increased surveillance of CJD in humans. Detection of earlier cases would suggest a shorter incubation period and might lead to predictions of epidemic size being revised. Methods: All certified deaths (excluding external injury and poisoning) in residents of Wales aged 15–45, between 1985 and 1995, were reviewed to detect vCJD deaths that might have been overlooked. 12 091 deaths were reviewed. "Non-specific fatal disorders compatible with vCJD" were defined. Deaths recorded to diseases other than those defined were rejected from further analysis (8769). Remaining cases (3322) were subdivided. Group A comprised deaths recorded to suicide, transport accidents, and those that could not be ascertained (ICD9 rubrics E950–959, E800–848, and 7999), a total of 2698 cases. Group B comprised deaths due to neurological disease, psychiatric disease, or substance abuse (624). Results: For group A, remaining brain material was identified (n=218, 8.1%) and examined by routine histology and immunocytochemistry for prion protein. No cases of vCJD were detected. For group B, review of remaining clinical information was undertaken. Of 624 cases, information was available on 447 (72%). Brain tissue was examined by routine histology and immunocytochemistry in 47 (7.5%) cases. Sufficient clinical and pathological information was available to exclude all these as potential cases of vCJD. Conclusion: Variant CJD is a new disease entity and not simply the result of better case ascertainment.